Use of periodicals in the Filipiniana and Special Collections Division, University of the Philippines, Diliman Main Library, June 1987 to September 1988 - Ponseca, Zenaida R. (1990)
The study was conducted to: 1) find out the categories of users who have a great demand for various types of periodicals; 2) determine what percentage of the entire periodical collection is frequently used; 3) identify which of the existing periodical titles in the Filipinina collection are frequently requested by the users; and 4) identify the topics/subjects frequently read/inquired into them.